Influence of Cable Lug Properties on the Torsional Ultrasonic Crimping Process of High-Frequency Litz Wires - Seefried, Johannes; Wieprecht, Nico; Franke, Jörg; Kühl, Alexander (2023 13th International Electric Drives Production Conference, EDPC 2023 - Proceedings, 2023)
The growing popularity of electromobility requires a continuous development of the associated charging infrastructure and the charging technologies used. Inductive charging systems, which enable a wireless power transfer (WPT) in the static and dynamic state of the electric vehicles, bear a great potential in this context. WPT is based on a ground coil and a coil on the vehicle side. The coils consist, among other components, of high-frequency litz wires, which are characterized by a high number of primary-insulated and stranded individual wires. During the production of the coil systems, this results in a wide range of challenges, especially for the contacting technology of the high-frequency litz wire. Thus, all individual wires of the litz wire must be stripped and electrically as well as mechanically terminated with contact elements. One of the processes used for this step is hot crimping, where the litz wires are crimped with tubular cable lugs and the primary insulation is thermally removed by resistance heating. Another process that has not yet been used in industrial series production is the torsional ultrasonic crimping process, which offers particular advantages in terms of process energy consumption. In order to further optimize this process, the influence of the tubular cable lugs used on the contact quality and various process variables is therefore analyzed in the context of this publication. The main focus is on the surface properties of the cable lugs.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Litz Wire; Ultrasonic Crimping; Ultrasonic Welding; Wireless Power Transfer